Taxonomia e diversidade dos Alysiinae (Hymenoptera: Braconidae) Neotropicais, com ênfase na fauna da Mata Atlântica, Brasil - Arouca, Raquel Gonçalves (2005)
The material studied comes from eighteen localities of Atlantic Forest from BIOTA/FAPESP Project: João Pessoa, PB; Recife, PE; Quebrangulo, AL; Santa Luzia do Itanhy, SE; Mata São João, BA; Mata da Esperança, BA: Porto Seguro, BA: Linhares, ES; Santa Teresa, ES; Santa Maria Madalena, RJ; Nova Iguaçu, RJ; Ubatuba, SP; Salesópolis, SP; Ribeirão Grande, SP; Peruíbe, SP; Morretes, PR; São Francisco do Sul, SC and São Bento do Sul, SC. Other specimens from the DCBU collection (Departamento de Ecologia e Biologia Evolutiva, Universidade Federal de São Carlos) were studies too. The material was collected using three techniques: Malaise traps, Moericke traps and sweeping vegetation. The amount of Alysiinae examined was 2.920 specimens (2.082 of BIOTA/FAPESP Project and 838 of other collection), identified in 14 genera. Dinotrema, Aphaereta e Phaenocarpa were the most frequent genera. Indices of Diversity and Equitability were used to discuss the richness and dominance of genera in each locality. The higher values of richness were recorded in Nova Iguaçu, RJ; São Bento do Sul, SC; São Francisco do Sul, SC; Santa Teresa, ES e Santa Luzia do Itanhy, SE and the lower in João Pessoa, PB; Recife, PE; Mata São João, BA; Porto Seguro, BA e Linhares, ES. These data evidenced a trend to the enrichment of the Alysiinae fauna to the Atlantic Forest areas in largest latitudes. The higher Diversity Index was recorded in Santa Luzia do Itanhy, SE and the lower in João Pessoa, PB. Linhares, ES presented the highest Equitability and Santa Teresa, ES the lower. Cluster Analysis was adopted taking as attribute the occurrence of the Alysiiinae genera. Four species of Phaenocarpa and Aphaereta confusa Wharton, 1994 female were described. Eight species were reported from Brazil for the first time: Gnathopleura carinata (Szépligeti, 1904); G. bugabensis (Cameron, 1887); G. semirufa (Brullé, 1846); Ilatha pulchripennis (Latreille, 1805); Idiasta delicata (Papp, 1969); Phaenocarpa pericarpa Wharton & Carrejo, 1999; P. cratomorpha Wharton, 1994 and Aphaereta confusa Wharton, 1994; and four new genera were identified. Those results show the importance and the need of the taxonomic and ecological studies on the subfamily Alysiinae, especially in the Neotropical region.